Neuroprotective insights into Agave cantala: dual modulation of neuroinflammation and oxidative stress by phytochemicals through integrated in silico and in vitro approaches - Selvi, P. Thamarai; R Srinivasan (Creative Pharma Assent, 2025)
Background: Neurodegenerative disorders such as Alzheimer’s and Parkinson’s are strongly associated with chronic neuroinflammation and oxidative stress. Phytochemicals from medicinal plants offer promising multitarget therapeutic potential. Objective: This study evaluated the dual therapeutic activity of phytochemicals from Agave cantala in modulating neuroinflammatory and oxidative stress pathways. Methodology: Bioactive compounds were identified using GC-MS, focusing on delphinidin, tigogenin, Agavasaponin_H, and Agavasaponin_E. Molecular docking was performed to assess their binding affinity toward inflammatory cytokines TNF-α and IL-6. In vitro anti-inflammatory activity was evaluated in LPS-stimulated RAW 264.7 macrophages by measuring TNF-α and IL-6 levels. Antioxidant activity was assessed through DPPH, ABTS, and FRAP assays. Results and Discussion: Docking studies revealed strong interactions of delphinidin and tigogenin with TNF-α and IL-6, suggesting effective inhibition. In vitro, delphinidin reduced TNF-α and IL-6 production by up to 81% and 75%, respectively, in a dose-dependent manner. Tigogenin and the saponins also showed notable cytokine suppression. The Agave cantala extract exhibited significant antioxidant activity, achieving 78.3% radical scavenging in the DPPH assay at 100 μg/mL. These results indicate that the identified phytochemicals modulate key inflammatory and oxidative pathways, supporting their multitarget action. Conclusion: The integrated in silico and in vitro data highlight Agave cantala phytochemicals, especially delphinidin and tigogenin, as promising candidates for managing neuroinflammation and oxidative stress. Further in vivo validation and pharmacokinetic profiling are recommended to support their clinical potential.